2011
DOI: 10.1039/c1nj20604d
|View full text |Cite
|
Sign up to set email alerts
|

Stability trends and tautomerization of chalcocyclopentadienes. The role of aromaticity

Abstract: International audienceThe stability trends and tautomerization processes within the family of chalcocyclopentadienes (CpXH, X = O, S, Se, Te) have been investigated through the use of high-level G3B3 and G2 ab initio, as well as B3LYP density functional theory calculations. All methods predict the 5-substituted derivative to be the least stable tautomer, with the only exception of the Te derivative. For X = O, Se the dominant forms are the 2- and the 1-substituted derivatives, respectively, whereas for S, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…For example, the tautomerization of chalcocyclopentadienes (CpXH, X = O, S, Se, Te; see Figure 22) was investigated by means of several indices including magnetic (NICS), structural (HOMA), and electronic (FLU) ones. 312 These compounds can exist in a form of three isomers: 1-, 2-, or 5-substituted. Two rotamers are possible for 1-and 2derivatives, leading to the keto−enol tautomeric equilibrium.…”
Section: Relationships Between Tautomerism H-bonding and Aromaticitymentioning
confidence: 99%
“…For example, the tautomerization of chalcocyclopentadienes (CpXH, X = O, S, Se, Te; see Figure 22) was investigated by means of several indices including magnetic (NICS), structural (HOMA), and electronic (FLU) ones. 312 These compounds can exist in a form of three isomers: 1-, 2-, or 5-substituted. Two rotamers are possible for 1-and 2derivatives, leading to the keto−enol tautomeric equilibrium.…”
Section: Relationships Between Tautomerism H-bonding and Aromaticitymentioning
confidence: 99%
“…The activation barriers connecting the different anions (see Figure 5) follow a similar trend, O < S Se, to that observed for the corresponding neutral compounds. [18] Also, as has been found for the neutral systems, the barriers are high enough to assume that, on deprotonation of the O-Iso1 and S-Iso1 compounds only the O-C5 and S-C5 anions should be observed. Similarly, only the 5Se and the 5Te anions should be detected in the gas phase after deprotonation of Se-Iso1 and Te-Iso1 derivatives.…”
Section: Resultsmentioning
confidence: 71%
“…found to depend significantly on the nature of the heteroatom. [18] For the oxygen-containing compounds only two isomers, namely Iso2 and Iso3 should be expected in the gas phase at room temperature, and the latter is the dominant one. For sulfur, a more or less equal distribution of the Iso2 and Iso3 isomers should be expected, whereas for Se, the Iso2 form becomes slightly dominant with respect to Iso3, and a small proportion (3 %) of Iso1 should also be expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarities of the structure of 1 , 2 , and Sb(C 5 H 5 ) 3 suggested that a computational investigation of the structure of As(C 5 H 5 ) 3 would be of interest. Calculations have been reported for the cyclopentadienyl arsines As[(C 5 (i-Pr) 4 H]Cl 2 (semiempirical methods), As(C 5 H 5 )H 2 (HF, MP2, DFT, , and coupled cluster methods), and As(C 5 H 5 )Cl 2 (DFT and coupled cluster methods); we are not aware of previous calculations on the tris(cyclopentadienyl)arsines themselves.…”
Section: Computational Resultsmentioning
confidence: 99%